ICT in Zambia – Green Informatics on Strategies and Technological Innovations - Musonda Kapatamoyo; Victor Mbumwae (International Telecommunications Society (ITS), 2022)
The concept of Green Strategies in the management of the environment has taken center stage world over. Zambia has not been left behind as it has ratified and adopted the concept of 'green economy' or 'green growth' through the declared priority theme for the United Nations Conference on Sustainable Development in 2012 (Rio+20) (Banda &Bass, 2014:3). The definition of green growth adopted by Zambia is "development that makes sustainable and equitable use of Zambia's natural resources within ecological limits through reinforcing the three cornerstones of sustainable development" (UNCSD, 2012: 46). The cornerstones or pillars of sustainable development are the economy, social welfare and environment. In its simplest expression, a green economy is low-carbon, resource efficient and socially inclusive. It is based on a model which underscores both economic growth and social and natural resources development as opposed to the 'brown' economic model which emphasizes economic growth over social and natural (Chileshe & Moonga, 2019). The concept of Green Economy applies much to the ICT sector as ICTs are a major contributor to environmental waste and pollution. The report of the International Telecommunications Union (ITU), the Global E-Waste Monitor 2020 reported that a record 53.6 million metric tons (Mt) of e-waste - discarded products with a battery or plug such as computers and mobile phones - is reported generated worldwide in 2019, up 9.2 Mt in five years. Toxic and hazardous substances such as mercury, brominated flame-retardants (BFR) or chlorofluorocarbons (CFCs) are found in many types of electronic equipment and pose severe risk to human health and the environment if not handled in an environmentally sound manner. (...)
Keywords: 330; SURF Green ICT Maturity Model; E-waste; Green ICT; Green informatics; Sustainability; Zambia